Body Condition Scores and Evaluation of Feeding Habits of Dogs and Cats at a Low Cost Veterinary Clinic and a General Practice - Stephanie A. Sapowicz; Deborah E. Linder; Lisa M. Freeman (The Scientific World Journal)
This study assessed body condition scores (BCS) and feeding habits for dogs and cats. Eighty-six cats and 229 dogs (and their owners) were enrolled from 2 clinics: a low cost clinic (n=149) and a general practice (n=166). BCS and body weight were recorded. Owners completed a survey which included animal age, sex, and breed; owner demographics; and feeding practices (e.g., diet, rationale for feeding practices). Owners from the low cost clinic had a significantly lower income (P<0.001) and education (P<0.001) compared to those from the general practice. Animals from the low cost clinic were younger (P<0.001) and dogs were less likely to be neutered (P<0.001). Overweight prevalence was 55% overall (P=0.083), with a significantly higher prevalence in the general practice for cats (44% versus 66%; P=0.046), but not for dogs (58% versus 53%; P=0.230). Multivariate analysis showed that only neuter status was significantly associated with BCS (P=0.004). Veterinarians were the most common source of nutritional information, though lack of accurate nutrition knowledge was common among all participants. These findings support the need for enhanced communication about optimal BCS and nutrition regardless of socioeconomic status.